2022
DOI: 10.1098/rspb.2022.0641
|View full text |Cite
|
Sign up to set email alerts
|

Immediate predation risk alters the relationship between potential and realised selection on male traits in the Trinidad guppyPoecilia reticulata

Abstract: Imminent predation risk affects mating behaviours in prey individuals in a multitude of ways that can theoretically impact the strength of sexual selection, as well as its operation on traits. However, empirical studies of the effects of imminent predation risk on sexual selection dynamics are still scarce. Here we explore how perceived predation affects: (1) the relationship between the opportunity for selection and the actual strength of selection on male traits; and (2) which traits contribute to male fitne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 83 publications
1
4
1
Order By: Relevance
“…First, we found that colorful males, with large areas of iridescence and intermediate areas of orange, achieved the highest levels GT (Figure 2). This combination of traits is also associated with reproductive success during cooperative matings in this same guppy population (Devigili et al 2015;Glavaschi et al 2022). Colorful males are expected to be more conspicuous and females should evade their coercive mating attempts more easily, contrary to our result.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…First, we found that colorful males, with large areas of iridescence and intermediate areas of orange, achieved the highest levels GT (Figure 2). This combination of traits is also associated with reproductive success during cooperative matings in this same guppy population (Devigili et al 2015;Glavaschi et al 2022). Colorful males are expected to be more conspicuous and females should evade their coercive mating attempts more easily, contrary to our result.…”
Section: Discussioncontrasting
confidence: 94%
“…If female choice and male sexual coercion impose different pressures on guppy male phenotypes (Becher and Magurran 2004), we should expect pre-mating traits to be related to our measure of GT performance in opposite ways compared to cooperative mating/reproductive success in this population (Devigili et al 2015, Cattelan et al 2020; Glavaschi et al 2022) and others (Blows et al 2003; Brooks and Endler 2001; Gordon et al 2015). More specifically, body size and male color, which are positively associated with mating success when females are sexually receptive, should be negatively associated with coercive mating success with unreceptive females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of polyandry, and hence the relative importance of postcopulatory components in determining male reproductive success can vary extremely among taxa and mating systems (Taylor et al, 2014) and drive the interspecific variation in the expression of male traits associated with mating and fertilization success (Simmons et al, 2017). However, the relative importance of pre‐ and postcopulatory success in determining a male's reproductive fitness can also vary within the same species, not only in association with alternative male phenotypes (Gage et al, 1995) but also as a consequence of the fluctuation of environmental conditions, such as, for example, food availability (Cattelan et al, 2020; Janicke et al, 2015; Winkler & Janicke, 2022), temperature (Gómez‐Llano et al, 2021; Londoño‐Nieto et al, 2023; Moiron et al, 2022; Vasudeva et al, 2014) or predation risk (Glavaschi et al, 2020, 2022). The effect of ecological variation on sexual selection dynamics may vary according to whether the organism is adapted or not to a specific change and may be therefore very specific (Miller & Svensson, 2014).…”
Section: Introductionmentioning
confidence: 99%